Belatacept prophylaxis against organ rejection in adult kidney-transplant recipients. Issue 2 (1st February 2016) - Del Bello, Arnaud; Marion, Olivier; Milongo, David; Rostaing, Lionel; Kamar, Nassim
ABSTRACT: End-stage renal disease is a major health problem worldwide, with kidney transplantation being the treatment of choice. Calcineurin inhibitors are still the cornerstone of immunosuppressive therapy. However, they have well-known nephrotoxic affects and increase the risk of cardiovascular disease and cancer. In contrast, belatacept is a biological immunosuppressive agent that inhibits the T-cell co-stimulation. It is approved by the US Food and Drug Administration and the European Medicine Agency for use in adult kidney-transplant recipients to prevent acute rejection. Developmental studies show that belatacept is as efficient as calcineurin inhibitors at preventing acute rejection. In addition, kidney function is better and cardiovascular risk factors are reduced in patients given belatacept. Herein, the authors review the published evidence concerning the efficacy and safety of belatacept and discuss its potential specific indications.